A method for catalytic separation and high-value utilization of fluorinated organic binders in retired new energy devices
By using rare earth photocatalytic material R-MOF@TiO2 in retired new energy devices for photothermal catalytic depolymerization and peeling, combined with directional fluorine deposition and phosphorus solidification technology of lanthanide metal oxides, the high-value components of new energy devices are solved. The problems of lossless peeling and high-value utilization of full components have achieved an efficient, low-cost and environmentally friendly peeling process.
Patent Information
- Application Number
- CN202410885066.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-03
AI Technical Summary
The prior art has problems such as high-value components lossless peeling and high-value utilization of the stripping process of retired new energy devices, which are difficult, high cost, high energy consumption, toxic by-products and low quality.
The rare earth photocatalytic material R-MOF@TiO2 is used to realize the depolymerization and peeling of high-value components of new energy devices and organic binders under photothermal reaction conditions, and the stepwise directional fluorine and phosphorus solidification are carried out through the lanthanide metal oxide. Synchronously realize the directional enrichment and purification of toxic elements such as depolymerized fluorine and phosphorus.
It has achieved efficient stripping of high-value components of new energy devices under mild conditions, reducing energy consumption and costs, avoiding toxic emissions of by-products, and achieving waste-free generation through high-value utilization throughout the entire process.
Smart Images

Figure CN118851119B_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to a three-phase waste comprehensive disposal technology in the process of stripping and recycling organic binders of retired new energy devices, and in particular to a method for catalytic separation and high-value utilization of fluorine-containing organic binders of retired new energy devices. Background technology:
[0002] Retired new energy devices include waste lithium-ion battery electrode materials, waste circuit boards and waste photovoltaic panels. Fluorinated organic binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluorinated styrene butadiene rubber (SBRF) and fluorinated carboxymethyl cellulose (CMCF) are often used to bond the device components. Ultrasonic-assisted organic solvent "similar dissolution" binders, high-temperature-assisted strong acid-base dissolution and mechanical crushing physical sorting are often used to strip organic binders for recycling pretreatment. Organic solvents can effectively strip high-value components and obtain complete low-value components by using the principle that solvents such as N-methylpyrrolidone and dimethylformamide are similarly soluble in binders. However, the cost of organic solvents and the harsh reaction conditions at low temperatures pose a great potential threat to the health of operators. High-temperature-assisted strong acid-base dissolution uses the difference in dissolution of two components to achieve the purpose of stripping high-value components. It is one of the methods commonly used in laboratories and industrial production lines. However, fluorinated organic binders and other organic components will emit a large amount of toxic and harmful gases at high temperatures, and the strong acid-base system will corrode the reaction equipment and cause salt-containing wastewater. Although mechanical crushing and physical sorting methods have less harm to the environment, the products are often mixed with a large number of low-value components, which increases the difficulty of subsequent high-value component impurity removal and purification, and requires further treatment. Publication No. CN116136022A discloses a stripping agent, a stripping liquid composition, and a stripping method for waste lithium-ion battery electrode materials. After the waste lithium-ion battery cells are cut into pieces, organic acid is used to separate the positive electrode material from the aluminum foil and the negative electrode material from the copper foil. The corrosion inhibitor is further used to improve the component recovery rate. Although the recovery rate and purity of the positive electrode material and the negative electrode material can reach more than 99%, the entire system requires multi-stage stripping, and a large amount of sulfur-containing wastewater and hydrogen will be discharged. The by-products of the reaction system are cheap, and it is difficult to achieve a green, safe and stable recovery process, and it is difficult to guarantee the economy and safety. Publication No. CN115871045A discloses a control system and control method for a photovoltaic panel hot knife stripping device, which uses a high-temperature hot knife to mechanically strip the back panel glass and battery silicon wafer film in the photovoltaic panel, and can effectively strip fluorine-containing organic matter and high-value components. However, the fluorine-containing organic matter will stick to the blade as the hot knife is stripped, greatly limiting the stripping efficiency of industrial production.
[0003] Based on the above analysis, whether it is possible to depolymerize the fluorinated binder on the surface of high-value components of retired new energy devices and strip off the high-value components, while achieving high-quality utilization of the low-value by-products generated in the process, is of great significance to the efficient stripping and recycling of energy devices.
[0004] Therefore, it is necessary to develop a new type of low-energy, low-pollution and low-cost energy device stripping method to solve the problem of lossless stripping of high-value components of energy devices and high-value utilization of all components during the stripping process. Summary of the invention:
[0005] The present invention provides a method for catalytic separation and high-value utilization of fluorine-containing organic binders of retired new energy devices. The method is based on the chemical property that photocatalysis can achieve depolymerization of organic matter under mild conditions, and is coupled with the characteristics and principles of rare earth metal lanthanum and toxic elements such as fluorine and phosphorus to more easily generate high-value chemicals. The depolymerization and stripping of high-value components of energy devices and organic binders are achieved under photothermal reaction conditions, and the directional enrichment and purification of depolymerized toxic elements such as fluorine and phosphorus are simultaneously achieved. The method not only solves the problems of low stripping rate of mechanical crushing and physical sorting methods and the discharge of toxic reactants and salt-containing wastewater in strong acid and alkali systems in chemical solvent methods, but also achieves the effect of no waste generation and high-value utilization of by-products in the whole process by coupling the recovery of waste photocatalysts and the preparation of optical materials, and solves the problems of difficulty, high cost, high energy consumption, and toxic and low-quality stripping of organic binders in the recovery process of high-value components of new energy devices.
[0006] A method for catalytic stripping and high-value utilization of fluorinated organic binders of retired new energy devices, the method comprising the following steps:
[0007] (1) Preparation of rare earth photocatalytic materials: lanthanide metal oxide, 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor for high temperature reaction at 400°C to 450°C for 7 to 12 hours. The molar ratio of lanthanide metal oxide, 4-isopropylbenzoic acid and ethylene carbonate was 1:1.4:1 to 1.5. The solution after high temperature reaction was centrifuged at 2°C to 7°C, dried, washed with ethanol and water for multiple times, and then calcined at 400 to 500°C under nitrogen for 15 to 26 hours to obtain a MOF catalyst carrier, named R-MOF, where R represents the type of lanthanide metal, selected from one of La, Ce, Pr, Nd, Sm and Eu. R-MOF, titanium tetra-n-butoxide and oxalic acid were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 -5 mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material R-MOF@TiO2; the mass ratio of R-MOF, titanium tetra-n-butoxide and oxalic acid is 1:3:0.4-1.4g / g;
[0008] (2) Photothermal catalytic depolymerization and stripping: The R-MOF@TiO2 obtained in step (1) and the retired new energy device are added to an isopropanol solution, and the temperature is adjusted after light exposure, high temperature, low pressure and enhanced stirring to achieve depolymerization of the fluorine-containing organic binder in the retired energy device to obtain high-value component monomers of the energy material device and fluorine-containing phosphorus mixed gas, and the high-value component monomers are returned to the energy device regeneration process; the light exposure, high temperature, low pressure and enhanced stirring, the xenon lamp light source has a luminous spectrum wavelength range of 300nm to 350nm, and a light intensity range of 120mW / cm 2 ~220mW / cm 2 , the temperature is 110-140°C, the nitrogen pressure is 0.05MPa-0.29MPa, the intensive stirring speed is 260rpm-385rpm, and the stirring time is 3h-13h;
[0009] (3) Acid leaching of lanthanum: The R-MOF@TiO4 with low catalytic efficiency obtained in step (2) is acid-leached for multiple cycles to obtain a lanthanum-rich leaching solution and titanium-rich slag, and the titanium-rich slag is returned to the electroplating solution production process;
[0010] (4) low temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain fluorine-containing lanthanum slag, defluorinated residual liquid and mixed gas; the mixed gas contains H2, CH4 and C2H6;
[0011] (5) Heating and purifying phosphorus fixation: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 1 to 2 using 75 to 80% by mass of H3PO4, and the temperature is raised to 80°C to 90°C to obtain phosphorus lanthanum slag. The phosphorus lanthanum slag is purified by alcohol washing and negative pressure heating volatilization to obtain high-purity RPO4, which can be directly used in the production of fluorescent materials. The water vapor is condensed and returned to step (2) for reuse.
[0012] Preferably, the retired new energy device comprises one of waste lithium-ion battery electrode materials, waste circuit boards and waste photovoltaic panels, and the fluorine-containing organic binder is one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluorinated styrene-butadiene rubber (SBRF) and fluorinated carboxymethyl cellulose (CMCF), preferably polyvinylidene fluoride (PVDF).
[0013] Preferably, the low-temperature centrifugation speed in step (1) is 500 to 1000 rpm.
[0014] Preferably, the mass ratio of the R-MOF@TiO2, retired new energy devices and isopropanol in step (2) is 1:10:22.7 to 1:10:29.
[0015] Preferably, the acid in step (3) is 0.1M to 2.1M H3PO4, and the stirring speed of the enhanced leaching is 300rpm to 425rpm.
[0016] Preferably, the fluorine-phosphorus mixed gas flow rate in step (4) is 10 mL / min to 20 mL / min, the temperature is 35 to 60° C., and the pH value ranges from 4 to 5.8.
[0017] Preferably, the alcohol washing in step (5) is performed with ethanol having a mass concentration of 70% to 85%, the insulation temperature is 120° C. to 145° C., the vacuum pressure is 2 to 5 Pa, and the insulation time is 1 h to 6 h.
[0018] Preferably, the high-value component monomers obtained in step (2) are returned to the energy device regeneration process; and the titanium-rich slag obtained in step (3) is returned to the electroplating solution production process.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. Compared with the traditional methods of stripping organic binders by using ultrasound-assisted organic solvents for "similar dissolution", high temperature-assisted strong acid and alkali dissolution, and mechanical crushing and physical sorting, the present invention uses lanthanide metal oxides and titanium dioxide and other low-cost and stable metal oxides to prepare rare earth photocatalytic materials R-MOF@TiO2, and utilizes the rich structure and ultra-large specific surface area of MOF materials to provide abundant reaction active sites for promoting the depolymerization and stripping of organic binders under auxiliary photothermal reaction conditions. Then, lanthanide metal oxides are used for step-by-step directional precipitation of fluorine and phosphorus, and waste photocatalysts are simultaneously acid-leached to reuse the lanthanum-rich leachate in the system, which can reduce the subsequent impurity element removal steps caused by the introduction of other elements and improve the removal rates of the two toxic elements of fluorine and phosphorus. It has the advantages of mild reaction conditions, environmentally friendly reaction system, and high stripping rate.
[0021] 2. The present invention uses photothermal catalysis to attack the carbon-fluorine bond in the fluorine-containing organic binder (such as PVDF) by isopropanol hydroxyl group, resulting in depolymerization and defluorination of the fluorine-containing organic binder. The coupling reaction generates gas to expand the distance between the fluorine-containing organic binder and the energy device, thereby achieving the stripping of the fluorine-containing organic binder and the energy device components. In addition, lanthanide metal compounds enriched with toxic elements such as fluorine and phosphorus are more likely to generate insoluble stable compounds, achieving a higher removal rate of toxic elements.
[0022] 3. The reuse of waste rare earth catalysts and the high-value utilization of products in the entire process not only reduce the mining of rare earth minerals, but also provide a new method for the synthesis of precursors of high-value optical materials, realizing a new path for the resource utilization and high-value utilization of waste catalysts. The entire system generates no waste, effectively reducing carbon emissions.
[0023] Therefore, the present invention adopts hydroxyl group to attack the carbon-fluorine bond in the organic binder to prepare the photocatalyst, and realizes the one-step photothermal catalytic depolymerization of the organic binder instead of the traditional mechanical crushing, sorting, strong acid and alkali leaching and other multi-step processes, which not only avoids the use of toxic and harmful solvents but also can prepare high-value products of toxic elements in the binder in a targeted manner, and can also achieve the effect of recycling the waste catalyst and retired energy devices by targeted preparation of catalyst types, which is particularly suitable for the stripping of organic binders of energy devices and the preparation of optical materials for the recycling of energy devices, and provides a safe, efficient and economical solid waste disposal and new material clean synthesis method for the recycling of retired new energy devices and the manufacturing of advanced materials. Description of the drawings:
[0024] Figure 1 This is the morphology of the photocatalyst obtained in Example 1 of the present invention.
[0025] Figure 2 This is the XRD phase composition diagram of the purified lanthanum phosphate obtained in Example 1 of the present invention.
[0026] Figure 3 This is the morphology of the purified lanthanum phosphate obtained in Example 1 of the present invention. Specific implementation method:
[0027] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0028] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.
[0029] The technical solution of the present invention is clearly and completely described below in conjunction with the embodiments of the present invention.
[0030] Example 1
[0031] A method for catalytic stripping and high-value utilization of organic matter from retired energy devices comprises the following steps:
[0032] (1) Preparation of rare earth photocatalytic materials: La2O3, 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor and subjected to a high temperature reaction at 400°C for 7 h. The solution after the high temperature reaction was centrifuged at 2°C at a speed of 500 rpm and then dried, washed with ethanol and water for multiple times, and calcined at 400°C for 15 h under nitrogen to obtain La-MOF. La-MOF, titanium tetra-n-butoxide and oxalic acid in a mass ratio of 1:3:0.4 g / g were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 -5mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material La-MOF@TiO2; wherein the molar ratio of La2O3 to 4-isopropylbenzoic acid and ethylene carbonate is 1:1.4:1.
[0033] (2) Photothermal catalytic depolymerization and stripping: the La-MOF@TiO2 obtained in step (1) and the waste lithium-ion battery electrode material are added to an isopropanol solution, and the temperature is adjusted after light exposure, high temperature, low pressure and intensive stirring to achieve depolymerization of PVDF in the waste lithium-ion battery electrode material, thereby obtaining high-value component monomers and fluorine-phosphorus mixed gas of energy material devices, and the high-value component monomers are returned to the energy device regeneration process; wherein the mass ratio of La-MOF@TiO2, waste lithium-ion battery electrode material and isopropanol is 1:10:22.7, the wavelength of the xenon lamp light source luminescence spectrum is 300nm, and the light intensity is 120mW / cm 2 , temperature is 110°C, nitrogen pressure is 0.05Mpa, enhanced stirring speed is 260rpm, and reaction time is 3h.
[0034] (3) Acid leaching of lanthanum: The La-MOF@TiO2 with low catalytic efficiency in the number of cycles in step (2) is leached with 0.1M H3PO4, and the stirring speed of the enhanced leaching is 300rpm. The lanthanum-rich leaching solution and titanium-rich slag are obtained, and the titanium-rich slag is returned to the electroplating solution production process;
[0035] (4) Low-temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain a fluorine-containing lanthanum slag, defluorination residual liquid, H2, CH4 and C2H6 mixed gas; the waste rare earth photocatalyst can come from the La-MOF@TiO2 that has reached the cycle number in step (2); wherein the flow rate of the fluorine-containing phosphorus mixed gas is 10 mL / min, the temperature is 35°C, and the pH value is 4.
[0036] (5) Heating and purifying phosphorus fixation: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 1 with 75% H3PO4 by mass, and the temperature is 80°C to obtain phosphorus lanthanum slag; the phosphorus lanthanum slag is purified by alcohol washing-negative pressure heating volatilization to obtain high-purity LaPO4 which can be directly used in the production of fluorescent materials, and the water vapor is condensed and returned to step (2) for reuse. The concentration of purified ethanol washing is 70%, the insulation temperature is 120°C, the vacuum pressure is 2Pa, and the insulation time is 1h.
[0037] Example 2
[0038] A method for catalytic stripping and high-value utilization of organic matter from retired energy devices comprises the following steps:
[0039] (1) Preparation of rare earth photocatalytic materials: CeO2, 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor and subjected to a high temperature reaction at 450°C for 12 h. The solution after the high temperature reaction was centrifuged at 7°C with a centrifugal speed of 1000 rpm, and then dried, washed with ethanol and water for multiple times, and calcined at 500°C for 26 h under nitrogen to obtain Ce-MOF. Ce-MOF, titanium tetra-n-butoxide and oxalic acid in a mass ratio of 1:3:1.4 g / g were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 - 5 mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material Ce-MOF@TiO2; wherein the molar ratio of CeO2 to 4-isopropylbenzoic acid and ethylene carbonate is 1:1.4:1.5.
[0040] (2) Photothermal catalytic depolymerization and stripping: Ce-MOF@TiO2 obtained in step (1) and waste lithium-ion battery electrode materials are added to an isopropanol solution, and the temperature is adjusted after light irradiation, high temperature, low pressure and intensive stirring to achieve depolymerization of PVDF in the waste lithium-ion battery electrode materials, thereby obtaining high-value component monomers and fluorine-containing phosphorus mixed gas for energy material devices, and the high-value component monomers are returned to the energy device regeneration process; wherein the mass ratio of Ce-MOF@TiO2, waste lithium-ion battery electrode materials and isopropanol is 1:10:29, the wavelength of the xenon lamp light source luminescence spectrum is 350nm, and the light intensity is 220mW / cm 2 , temperature is 140°C, nitrogen pressure is 0.29MPa, enhanced stirring speed is 385rpm, and reaction time is 13h.
[0041] (3) Acid leaching of lanthanum: Ce-MOF@TiO2 with low catalytic efficiency in the number of cycles in step (2) is leached with 2.1M H3PO4, and the stirring speed of the enhanced leaching is 425rpm. Lanthanum-rich leaching solution and titanium-rich slag are obtained, and the titanium-rich slag is returned to the electroplating solution production process;
[0042] (4) Low-temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain a fluorine-containing lanthanum slag, defluorination residual liquid, H2, CH4 and C2H6 mixed gas; the waste rare earth photocatalyst can come from the Ce-MOF@TiO2 that has reached the cycle number in step (2); wherein the flow rate of the fluorine-containing phosphorus mixed gas is 20 mL / min, the temperature is 60°C, and the pH value is 5.5.
[0043] (5) Heating and purifying phosphorus fixation: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 2 with 80% H3PO4 by mass, and the temperature is 90°C to obtain phosphorus lanthanum slag; the phosphorus lanthanum slag is purified by alcohol washing-negative pressure heating volatilization to obtain high-purity CePO4 which can be directly used in the production of fluorescent materials, and the water vapor is condensed and returned to step (2) for reuse. The concentration of purified ethanol washing is 85%, the insulation temperature is 145°C, the vacuum pressure is 5Pa, and the insulation time is 6h.
[0044] Example 3
[0045] A method for catalytic stripping and high-value utilization of organic matter from retired energy devices comprises the following steps:
[0046] (1) Preparation of rare earth photocatalytic materials: Pr6O 11 , 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor and subjected to a high temperature reaction at 410°C for 8 hours. The solution after the high temperature reaction was centrifuged at 3°C at a centrifugal speed of 600 rpm and then dried, washed with ethanol and water for multiple times, and calcined at 420°C under nitrogen for 17 hours to obtain Pr-MOF; Pr-MOF, titanium tetra-n-butoxide and oxalic acid in a mass ratio of 1:3:0.6 g / g were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 - 5 mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material Pr-MOF@TiO2; among them, Pr6O 11 The molar ratio of 4-isopropylbenzoic acid to ethylene carbonate is 1:1.4:1.1.
[0047] (2) Photothermal catalytic depolymerization and stripping: Pr-MOF@TiO2 obtained in step (1) and waste lithium-ion battery electrode materials are added to an isopropanol solution, and the temperature is adjusted after light exposure, high temperature, low pressure and intensive stirring to achieve depolymerization of PVDF in the waste lithium-ion battery electrode materials, thereby obtaining high-value component monomers and fluorine-containing phosphorus mixed gas for energy material devices, and the high-value component monomers are returned to the energy device regeneration process; wherein the mass ratio of Pr-MOF@TiO2, waste lithium-ion battery electrode materials and isopropanol is 1:10:23.75, the wavelength of the xenon lamp light source luminescence spectrum is 310nm, and the light intensity is 220mW / cm 2 , temperature is 120°C, nitrogen pressure is 0.09MPa, enhanced stirring speed is 285rpm, and reaction time is 5h.
[0048] (3) Acid leaching of lanthanum: The Pr-MOF@TiO2 with low catalytic efficiency in the number of cycles in step (2) is leached with 0.5M H3PO4, and the stirring speed of the enhanced leaching is 325rpm. Lanthanum-rich leaching solution and titanium-rich slag are obtained, and the titanium-rich slag is returned to the electroplating solution production process;
[0049] (4) Low-temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain a fluorine-containing lanthanum slag, defluorination residual liquid, H2, CH4 and C2H6 mixed gas; the waste rare earth photocatalyst can come from the Pr-MOF@TiO2 that has reached the cycle number in step (2); wherein the flow rate of the fluorine-containing phosphorus mixed gas is 12 mL / min, the temperature is 40°C, and the pH value is 4.3.
[0050] (5) Heating and purifying phosphorus fixation: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 1.2 with 76% H3PO4 by mass, and the temperature is 82°C to obtain phosphorus lanthanum slag; the phosphorus lanthanum slag is purified by alcohol washing-negative pressure heating volatilization to obtain high-purity PrPO4 which can be directly used in the production of fluorescent materials, and the water vapor is condensed and returned to step (2) for reuse. The concentration of purified ethanol washing is 73%, the insulation temperature is 125°C, the vacuum pressure is 2.6 Pa, and the insulation time is 2h.
[0051] Example 4
[0052] A method for catalytic stripping and high-value utilization of organic matter from retired energy devices comprises the following steps:
[0053] (1) Preparation of rare earth photocatalytic materials: Nd2O3, 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor and subjected to a high temperature reaction at 440°C for 11 h. The solution after the high temperature reaction was centrifuged at 6°C at a speed of 900 rpm, and then dried, washed with ethanol and water for multiple times, and calcined at 480°C under nitrogen for 24 h to obtain Nd-MOF. Nd-MOF, titanium tetra-n-butoxide and oxalic acid in a mass ratio of 1:3:1.2 g / g were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 - 5 mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material Nd-MOF@TiO2; wherein the molar ratio of Nd2O3 to 4-isopropylbenzoic acid and ethylene carbonate is 1:1.4:1.4.
[0054] (2) Photothermal catalytic depolymerization and stripping: the Nd-MOF@TiO2 obtained in step (1) and the waste lithium-ion battery electrode material are added to an isopropanol solution, and the temperature is adjusted after light exposure, high temperature, low pressure and intensive stirring to achieve depolymerization of PVDF in the waste lithium-ion battery electrode material, thereby obtaining high-value component monomers and fluorine-containing phosphorus mixed gas for energy material devices, and the high-value component monomers are returned to the energy device regeneration process; wherein the mass ratio of Nd-MOF@TiO2, waste lithium-ion battery electrode material and isopropanol is 1:10:27.95, the wavelength of the xenon lamp light source luminescence spectrum is 340nm, and the light intensity is 200mW / cm 2, temperature is 135°C, nitrogen pressure is 0.25MPa, enhanced stirring speed is 360rpm, and reaction time is 11h.
[0055] (3) Acid leaching of lanthanum: The Nd-MOF@TiO2 with low catalytic efficiency in the number of cycles in step (2) is leached with 1.7M H3PO4, and the stirring speed of the enhanced leaching is 400rpm. Lanthanum-rich leaching solution and titanium-rich slag are obtained, and the titanium-rich slag is returned to the electroplating solution production process;
[0056] (4) Low-temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain a fluorine-containing lanthanum slag, defluorination residual liquid, H2, CH4 and C2H6 mixed gas; the waste rare earth photocatalyst can come from the Nd-MOF@TiO2 that has reached the cycle number in step (2); wherein the flow rate of the fluorine-containing phosphorus mixed gas is 18 mL / min, the temperature is 55°C, and the pH value is 5.2.
[0057] (5) Heating and purifying phosphorus fixation: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 1.8 with 79% H3PO4 by mass, and the temperature is 88°C to obtain phosphorus lanthanum slag; the phosphorus lanthanum slag is purified by alcohol washing-negative pressure heating volatilization to obtain high-purity NdPO4 which can be directly used in the production of fluorescent materials, and the water vapor is condensed and returned to step (2) for reuse. The concentration of purified ethanol washing is 82%, the insulation temperature is 140°C, the vacuum pressure is 4.4 Pa, and the insulation time is 5h.
[0058] Example 5
[0059] A method for catalytic stripping and high-value utilization of organic matter from retired energy devices comprises the following steps:
[0060] (1) Preparation of rare earth photocatalytic materials: SmO, 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor and subjected to a high temperature reaction at 420°C for 9 h. The solution after the high temperature reaction was centrifuged at 4°C at a speed of 900 rpm, and then dried, washed with ethanol and water for multiple times, and calcined at 440°C for 19 h under nitrogen to obtain Sm-MOF. Sm-MOF, titanium tetra-n-butoxide and oxalic acid in a mass ratio of 1:3:0.8 g / g were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 - 5 mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material Sm-MOF@TiO2; wherein the molar ratio of SmO to 4-isopropylbenzoic acid and ethylene carbonate is 1:1.4:1.2.
[0061] (2) Photothermal catalytic depolymerization and stripping: The Sm-MOF@TiO2 obtained in step (1) and the waste lithium-ion battery electrode material are added to an isopropanol solution, and the temperature is adjusted after light exposure, high temperature, low pressure and intensive stirring to achieve depolymerization of PVDF in the retired energy device, thereby obtaining high-value component monomers of the energy material device and fluorine-phosphorus mixed gas, and the high-value component monomers are returned to the energy device regeneration process; wherein the mass ratio of Sm-MOF@TiO2, waste lithium-ion battery electrode material and isopropanol is 1:10:25.85, the xenon lamp light source has a luminous spectrum wavelength of 320nm, and a light intensity of 160mW / cm 2 , temperature is 125°C, nitrogen pressure is 0.17MPa, enhanced stirring speed is 310rpm, and reaction time is 7h.
[0062] (3) Acid leaching of lanthanum: The Sm-MOF@TiO2 with low catalytic efficiency in the number of cycles in step (2) is leached with 0.9M H3PO4, and the stirring speed of the enhanced leaching is 350rpm. Lanthanum-rich leaching solution and titanium-rich slag are obtained, and the titanium-rich slag is returned to the electroplating solution production process;
[0063] (4) Low-temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain a fluorine-containing lanthanum slag, defluorination residual liquid, H2, CH4 and C2H6 mixed gas; the waste rare earth photocatalyst can come from the Sm-MOF@TiO2 that has reached the cycle number in step (2); wherein the flow rate of the fluorine-containing phosphorus mixed gas is 14 mL / min, the temperature is 45°C, and the pH value is 5.2.
[0064] (5) Heating and solidifying phosphorus for purification: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 1.4 with 77% H3PO4 by mass, and the temperature is 84°C to obtain phosphorus lanthanum slag; the phosphorus lanthanum slag is purified by alcohol washing-negative pressure heating volatilization to obtain high-purity Sm3(PO4)2, which can be directly used in the production of fluorescent materials, and the water vapor is condensed and returned to step (2) for reuse. The concentration of purified ethanol washing is 76%, the insulation temperature is 130°C, the vacuum pressure is 3.2 Pa, and the insulation time is 3h.
[0065] Example 6
[0066] A method for catalytic stripping and high-value utilization of organic matter from retired energy devices comprises the following steps:
[0067] (1) Preparation of rare earth photocatalytic materials: Eu2O3, 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor and subjected to a high temperature reaction at 430°C for 10 h. The solution after the high temperature reaction was centrifuged at 5°C with a centrifugal speed of 800 rpm, and then dried, washed with ethanol and water for multiple times, and calcined at 460°C under nitrogen for 21 h to obtain Eu-MOF. Eu-MOF, titanium tetra-n-butoxide and oxalic acid in a mass ratio of 1:3:1 g / g were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 -5 mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material Eu-MOF@TiO2; wherein the molar ratio of Eu2O3 to 4-isopropylbenzoic acid and ethylene carbonate is 1:1.4:1.3.
[0068] (2) Photothermal catalytic depolymerization and stripping: The Eu-MOF@TiO2 obtained in step (1) and the waste lithium-ion battery electrode material are added to an isopropanol solution, and the temperature is adjusted after light exposure, high temperature, low pressure and intensive stirring to achieve PVDF depolymerization in the retired energy device, thereby obtaining high-value component monomers of the energy material device and fluorine-phosphorus mixed gas, and the high-value component monomers are returned to the energy device regeneration process; wherein the mass ratio of Eu-MOF@TiO2, waste lithium-ion battery electrode material and isopropanol is 1:10:26.9, the xenon lamp light source has a luminous spectrum wavelength of 330nm, and a light intensity of 180mW / cm 2 , temperature is 130°C, nitrogen pressure is 0.21MPa, enhanced stirring speed is 335rpm, and reaction time is 9h.
[0069] (3) Acid leaching of lanthanum: The Eu-MOF@TiO2 with low catalytic efficiency in the number of cycles in step (2) is leached with 1.3M H3PO4, and the stirring speed of the enhanced leaching is 375rpm. Lanthanum-rich leaching solution and titanium-rich slag are obtained, and the titanium-rich slag is returned to the electroplating solution production process;
[0070] (4) Low-temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain a fluorine-containing lanthanum slag, defluorination residual liquid, H2, CH4 and C2H6 mixed gas; the waste rare earth photocatalyst can come from the Eu-MOF@TiO2 that has reached the cycle number in step (2); wherein the flow rate of the fluorine-containing phosphorus mixed gas is 16 mL / min, the temperature is 50°C, and the pH value is 4.9.
[0071] (5) Heating and purifying phosphorus fixation: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 1.6 with 78% H3PO4 by mass, and the temperature is 86°C to obtain phosphorus lanthanum slag; the phosphorus lanthanum slag is purified by alcohol washing-negative pressure heating volatilization to obtain high-purity EuPO4 which can be directly used in the production of fluorescent materials, and the water vapor is condensed and returned to step (2) for reuse. The concentration of purified ethanol washing is 79%, the insulation temperature is 135°C, the vacuum pressure is 3.8 Pa, and the insulation time is 4 hours.
[0072] Comparative Example 1
[0073] A method for catalytic separation and high-value utilization of fluorine-containing binders of retired energy devices, referring to Example 2, except that the photothermal catalytic depolymerization and stripping process does not use heating but only uses light irradiation, and the rest of the process and parameters are the same as Example 2.
[0074] Since the photothermal catalytic depolymerization and stripping process in Comparative Example 1 was not heated, the toxic elements fluorine and phosphorus in the binder were not completely vaporized and attached to the surface of the high-value component monomers in large quantities, resulting in additional steps for impurity removal in each link, and the diffusion capacity between groups was weakened, resulting in a very low cost increase in the stripping rate, and the purpose of high value was not achieved.
[0075] Comparative Example 2
[0076] A method for catalytic separation and high-value utilization of fluorine-containing binders in retired energy devices, referring to Example 2, except that the photothermal catalytic depolymerization and stripping process only involves heating without light irradiation, and the rest of the process and parameters are the same as those in Example 2.
[0077] Since no photocatalytic reaction occurs in Example 2, the hydroxyl group cannot attack and replace the fluorine atom, resulting in difficulty in depolymerization of PVDF and a very low stripping rate. Only unstable PVDF is thermally denatured and ineffective, and the toxic fluorine element is not converted into a directional product, resulting in difficulty in defluorination. Effective stripping of retired energy device components and efficient recovery of high-value components cannot be achieved.
[0078] The organic binder stripping rates and residual amounts of impurity elements in Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1:
[0079] Table 1
[0080]
[0081] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for catalytic separation and high-value utilization of fluorinated organic binders in retired new energy devices, characterized in that: The method comprises the following steps: (1) Preparation of rare earth photocatalytic materials: lanthanide metal oxide, 4-isopropylbenzoic acid and ethylene carbonate were placed in a microwave reactor for high temperature reaction at 400°C to 450°C for 7 to 12 hours. The molar ratio of lanthanide metal oxide, 4-isopropylbenzoic acid and ethylene carbonate was 1:1.4:1 to 1.
5. The solution after high temperature reaction was centrifuged at 2°C to 7°C, dried, washed with ethanol and water for multiple times, and then calcined at 400 to 500°C under nitrogen for 15 to 26 hours to obtain a MOF catalyst carrier, named R-MOF, where R represents the type of lanthanide metal, selected from one of La, Ce, Pr, Nd, Sm and Eu. R-MOF, titanium tetra-n-butoxide and oxalic acid were added to deionized water and transferred to a rotary evaporator, and the vacuum degree was maintained at 10 -4 ~10 -5 mbar, until the water evaporates and dries to prepare the nano-sized rare earth photocatalytic material R-MOF@TiO2; the mass ratio of R-MOF, titanium tetra-n-butoxide and oxalic acid is 1:3:0.4-1.4; (2) Photothermal catalytic depolymerization and stripping: The R-MOF@TiO2 obtained in step (1) and the retired new energy device are added to an isopropanol solution, and the temperature is adjusted after light exposure, high temperature, low pressure and enhanced stirring to achieve depolymerization of the fluorine-containing organic binder in the retired new energy device to obtain high-value component monomers of the energy material device and fluorine-containing phosphorus mixed gas; the light exposure, high temperature, low pressure and enhanced stirring, the xenon lamp light source has a luminous spectrum wavelength range of 300nm to 350nm, and a light intensity range of 120mW / cm 2 ~220mW / cm 2 , the temperature is 110-140°C, the nitrogen pressure is 0.05MPa-0.29MPa, the intensive stirring speed is 260rpm-385rpm, and the stirring time is 3h-13h; (3) Acid leaching of lanthanum: The R-MOF@TiO2 with low catalytic efficiency obtained in step (2) is acid-leached for multiple cycles to obtain a lanthanum-rich leachate and titanium-rich slag; (4) low temperature fluorine precipitation: the fluorine-containing phosphorus mixed gas obtained in step (2) is introduced into the lanthanum-rich leaching solution obtained in step (3) at a certain flow rate for microwave mechanical stirring to obtain fluorine-containing lanthanum slag, defluorination residual liquid and mixed gas, wherein the mixed gas contains H2, CH4 and C2H6; (5) Heating and purifying phosphorus fixation: The defluorinated residual liquid obtained in step (4) is adjusted to a pH value of 1 to 2 using 75 to 80% by mass of H3PO4, and the temperature is raised to 80°C to 90°C to obtain phosphorus lanthanum slag. The phosphorus lanthanum slag is purified by alcohol washing and negative pressure heating volatilization to obtain high-purity RPO4 which is directly used in the production of fluorescent materials. The water vapor is condensed and returned to step (2) for reuse.
2. The method according to claim 1, characterized in that The retired new energy device is one of waste lithium-ion battery electrode materials, waste circuit boards and waste photovoltaic panels.
3. The method according to claim 1, characterized in that The fluorine-containing organic binder is one of polyvinylidene fluoride, polytetrafluoroethylene, fluorine-containing styrene-butadiene rubber and fluorine-containing carboxymethyl cellulose.
4. The method according to claim 1, characterized in that The rotation speed of the low-temperature centrifugation in step (1) is 500 to 1000 rpm.
5. The method according to claim 1, characterized in that The mass ratio of R-MOF@TiO2, retired new energy devices and isopropanol described in step (2) is 1:10:22.7-29.
6. The method according to claim 1, characterized in that The acid in step (3) is 0.1M to 2.1M H3PO4, and the stirring speed of the enhanced leaching is 300rpm to 425rpm.
7. The method according to claim 1, characterized in that The flow rate of the fluorine-phosphorus mixed gas in step (4) is 10 mL / min to 20 mL / min, the temperature is 35 to 60° C., and the pH value ranges from 4 to 5.
8.
8. The method according to claim 1, characterized in that The alcohol washing in step (5) is performed with ethanol having a mass concentration of 70% to 85%, the insulation temperature is 120° C. to 145° C., the vacuum pressure is 2 to 5 Pa, and the insulation time is 1 h to 6 h.
9. The method according to claim 1, characterized in that: The high-value component monomers obtained in step (2) are returned to the energy device regeneration process; and the titanium-rich slag obtained in step (3) is returned to the electroplating solution production process.
Citation Information
Patent Citations
Photovoltaic panel heat knife stripping device control system and control method thereof
CN115871045A
Stripping agent, stripping liquid composition and stripping method of waste lithium ion battery electrode material
CN116136022A
Regeneration method of waste nickel-cobalt-manganese ternary positive electrode material and positive electrode material
CN117199601A
KR20220113066A